Strengthening Rwanda's hybrid maize seed systems through agrodealers - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
Kilimo General Business (KGB) specialises in producing hybrid maize seeds across Rwanda. The Great Lakes Accelerated Innovation Delivery Initiative Rapid Delivery Hub (AID-I GLR) project has partnered with KGB to create awareness and enhance adoption of hybrid maize seeds through strengthened marketing strategies with agrodealers linking to farmers. In the video, hear how this model works from agrodealer Josette Twizere and Angelique Maniraguha, a farmer.